Initial Value Problems for Hybrid Generalized Hilfer Fractional Differential Equations - Salim, Abdelkrim; Lazreg, Jamal Eddine; Abbas, Said; Benchohra, Mouffak; Zhou, Yong (Discontinuity, Nonlinearity, and Complexity, 2026)
This manuscript is devoted to proving some results concerning the existence of solutions for a class of initial value problems for nonlinear fractional Hybrid differential equations and Generalized Hilfer fractional derivative. The result is based on a fixed point theorem due to Dhage. Further, some examples are provided for the justification of our main results.